2016 Heat Monitor: "Second rent" lower despite higher heating energy consumption - Claus Michelsen; Nolan Ritter (DIW Economic Bulletin, 2017)
Residential heating is responsible for one-fifth of Germany's energy consumption. Heating costs were around 562 euros per year for an average apartment in 2016, which is more than a 13th month's rent minus heating costs (Kaltmiete). These are the findings of the 2016 Heat Monitor, published by the German Institute for Economic Research and ista Deutschland GmbH. The report presents evaluations based on an extensive database of heating bills for apartment buildings in Germany. Apartment buildings constitute almost one-half of the total housing stock in Germany. Adjusted for climate and weather, their heating energy consumption rose by around two percent in comparison to 2015. However, a further drop in energy prices provided relief to private households once again. Throughout Germany energy prices decreased by around six percent compared to 2015. But this trend will not continue: energy prices are expected to remain constant or to rise slightly in upcoming heating periods. In the light of these developments and alongside climate policy considerations, it would be shortsighted to reduce effort in retrofitting buildings. After all, energy costs are the major determinant of the 'second rent.'
Keywords: R31; Q21; Q40; 330; apartment buildings; energy efficiency; residential heating energy demand